2022
DOI: 10.1108/sr-08-2021-0272
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic diagnosis method for stainless steel weld defects based on multi-domain feature fusion

Abstract: Purpose This paper aims to propose a new ultrasonic diagnosis method for stainless steel weld defects based on multi-domain feature fusion to solve two problems in the ultrasonic diagnosis of austenitic stainless steel weld defects. These are insufficient feature extraction and subjective dependence of diagnosis model parameters. Design/methodology/approach To express the richness of the one-dimensional (1D) signal information, the 1D ultrasonic testing signal was derived to the two-dimensional (2D) time-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…To solve the problem of ultrasonic diagnosis of defects in austenitic stainless steel, Zhang R. et al proposed a new defect diagnosis method based on multi-domain data FF. The experimental results showed that this method has comprehensively improved the performance of defect diagnosis and had a driving effect on ultrasonic missing element diagnosis [23]. Cui X. et al proposed a classification model by fusing image features and depth features to improve the performance of the MRI aided diagnosis model.…”
Section: Related Workmentioning
confidence: 99%
“…To solve the problem of ultrasonic diagnosis of defects in austenitic stainless steel, Zhang R. et al proposed a new defect diagnosis method based on multi-domain data FF. The experimental results showed that this method has comprehensively improved the performance of defect diagnosis and had a driving effect on ultrasonic missing element diagnosis [23]. Cui X. et al proposed a classification model by fusing image features and depth features to improve the performance of the MRI aided diagnosis model.…”
Section: Related Workmentioning
confidence: 99%
“…The four types of sub-macroscopic defects above includes pores and slag inclusions, which may include oxides, sulfides, silicates and their combination [43,[49][50][51][52][53]. The time domain waveforms of four types of defects are distinct, which illustrates the various components of them.…”
Section: Data Set Generation Under Optimal Testing Conditionsmentioning
confidence: 99%